Physical activity among children and young people with intellectual disabilities in special schools: Teacher and learning support assistant perceptions. (3rd December 2019) - Pierce, Samuel; Maher, Anthony J.
Accessible summary: We talked to teachers and learning support assistants about physical activity opportunities in school for children and young people with intellectual disabilities. Schools require a lot of space to support physical activity. Schools need specialist equipment to help children and young people to be physically active. It is better for children and young people to do physical activities that are suited to them. Abstract: Background: Despite well‐established benefits of engaging in regular physical activity, children and young people with intellectual disabilities are significantly less active than their age peers. Methods: Semi‐structured interviews were conducted with two teachers of PE and two learning support assistants working in special schools in order to provide an insight into the physical activity tendencies of children and young people (CYP) with intellectual disabilities. Results: Access to and use of outdoor spaces was claimed to have a positive impact on the physical activity tendencies of CYP with intellectual disabilities. However, the schools we visited had limited indoor space, which impacted negatively on the duration and frequency of physical activity that CYP were able to engage in, particularly when space had to be shared because of timetabling issues and unfavourable weather. When it came to the "type" of physical activities, individual, self‐initiated and self‐regulated were favoured. Conclusions: We end by suggesting that the onus is on teachers and learning support assistants to think of creative ways of using limited indoor space. The use of dining and assembly halls may be one solution. So, too, may be more individualised physical activities because they are often better suited to the needs and capabilities of CYP, and can often be performed in limited space.